1997
DOI: 10.1172/jci119191
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide (NO) modulates the neurogenic control of blood pressure in rats with chronic renal failure (CRF).

Abstract: Increased sympathetic nervous system (SNS) activity plays a role in the genesis of hypertension in rats with chronic renal failure (CRF). Because nitric oxide (NO) modulates the activity of the SNS, a deficit of NO synthesis could be responsible for the increased SNS activity in these animals.In the present study, we evaluated the effects of L -arginine and L-NAME on blood pressure and SNS activity in Sprague Dawley 5/6 nephrectomized or sham-operated rats. SNS activity was determined by measuring norepinephri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(66 citation statements)
references
References 56 publications
7
57
0
2
Order By: Relevance
“…A substantial body of work has shown that central or peripheral blockade of NO synthesis potentiates or prolongs the pressor response to ANG II (9,28,31,33), upregulates AT 1 expression, and activates cardiovascular angiotensin-converting enzyme (49). On the other hand, ANG II has been found to regulate NOS activity and NO release (27,57). Li et al (28) reported that push-pull administration of ANG II into the PVN induced an increase in NO release.…”
Section: Discussionmentioning
confidence: 99%
“…A substantial body of work has shown that central or peripheral blockade of NO synthesis potentiates or prolongs the pressor response to ANG II (9,28,31,33), upregulates AT 1 expression, and activates cardiovascular angiotensin-converting enzyme (49). On the other hand, ANG II has been found to regulate NOS activity and NO release (27,57). Li et al (28) reported that push-pull administration of ANG II into the PVN induced an increase in NO release.…”
Section: Discussionmentioning
confidence: 99%
“…In this model of neurogenic hypertension, the increase in BP is caused by injecting 50 l of 10% phenol into the lower pole of one kidney. 33 Injection of phenol leads to an immediate rise in BP, norepinephrine secretion from the posterior hypothalamus, and renal sympathetic nerve activation, which again can be prevented by renal denervation. 33 Of note, these effects are long lasting and do not occur with infusion of vehicle.…”
Section: Renal Injury and Ischemiamentioning
confidence: 99%
“…33 Injection of phenol leads to an immediate rise in BP, norepinephrine secretion from the posterior hypothalamus, and renal sympathetic nerve activation, which again can be prevented by renal denervation. 33 Of note, these effects are long lasting and do not occur with infusion of vehicle. 34 In conjunction with the demonstration of elevated sympathetic activity in experimental renal artery stenosis 35 Figure 1.…”
Section: Renal Injury and Ischemiamentioning
confidence: 99%
See 1 more Smart Citation
“…However, the mechanism for autonomic regulation of arterial pressure in responses to a dramatic rise in circulating catecholamines during transition is not known. Recent studies (34) have reported that the NE turnover rate in brain nuclei is associated with nNOS mRNA expression and NO content in chronic renal failure rats. In adult rats, coexistence of NADPHd/nNOS and TH in brain nuclei has been demonstrated and suggests that noradrenergic neurons are capable of generating NO for regulation of noradrenergic activity within the brain (25,31).…”
Section: Discussionmentioning
confidence: 99%